INOVASI PEMBELAJARAN IPAS MELALUI PROJECT BASED LEARNING BERBASIS MEDIA DIORAMA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Darlisa, Ratu; Fatimah; Asrul Karim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creative thinking ability is one of the important skills that needs to be developed in 21st-century learning, particularly at the elementary school level. However, science learning in elementary schools is still often teacher-centered, resulting in limited student involvement during the learning process. This study aims to improve students' creative thinking abilities through the implementation of the Project Based Learning model assisted by diorama media in science learning. This study used a qualitative approach with Classroom Action Research (CAR) conducted in three cycles. The subjects of this study were 25 fifth-grade students at UPTD SD Negeri 4 Bireuen. Data collection techniques included tests, observations, questionnaires, and documentation, while data analysis was conducted descriptively using percentages. The results showed that students' creative thinking abilities improved in each cycle. The percentage of students' classical mastery increased from 56% in Cycle I to 80% in Cycle II and reached 92% in Cycle III. Teacher activity increased from 86.3% to 94.5%, while student activity increased from 83.6% to 89%. In addition, students' responses toward the learning process showed a very positive category with a percentage of 98%. Based on these findings, it can be concluded that the implementation of the Project Based Learning model assisted by diorama media is effective in improving students' creative thinking abilities and creating science learning that is more active, engaging, and meaningful.